2020
DOI: 10.1016/j.jfo.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The trabecular meshwork: Structure, function and clinical implications. A review of the literature

Abstract: Glaucoma is a blinding optic neuropathy, the main risk factor for which is increased intraocular pressure (IOP). The trabecular meshwork, located within the iridocorneal angle, is the main pathway for drainage of aqueous humor (AH) out of the eye, and its dysfunction is responsible for the IOP elevation. The trabecular meshwork is a complex, fenestrated, threedimensional structure composed of trabecular meshwork cells (TMC) interdigitated into a multilayered organization within the extracellular matrix (ECM). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 115 publications
0
71
0
6
Order By: Relevance
“…This differs from the ultrastructure of the TM described in patients with PG. 1 , 2 , 4 , 11 , 12 Further study is necessary to determine how these pigment particles enter the cells in DBA/2J mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This differs from the ultrastructure of the TM described in patients with PG. 1 , 2 , 4 , 11 , 12 Further study is necessary to determine how these pigment particles enter the cells in DBA/2J mice.…”
Section: Discussionmentioning
confidence: 99%
“…As an important component of the aqueous drainage structures, the TM is composed of microtubular structures that form connections, with gaps of varying sizes in between. 11 , 12 The diameters and contractility of these microtubules and gaps determine their maximum passing capacity. Based on our preliminary research, we speculated that there is a maximum permeable diameter (MPD) for pigment particles to pass all the way through the TM via the aqueous convection current.…”
mentioning
confidence: 99%
“…POAG is an chronic, multifactorial optic neuropathy characterized by progressive loss of retinal ganglion cell (RGC) axons resulting in gradual loss of peripheral vision [1,16]. The trabecular meshwork (TM), a fenestrated structure located within the iridocorneal angle, is the main pathway for aqueous humour drainage and its dysfunction is largely responsible for IOP elevation [17,18]. The lamina cribrosa (LC), a mesh-like connective tissue structure at optic nerve head through which unmyelinated RGC axons pass as they exit the eye, is a key site of RGC axonal injury in POAG [19,20].…”
Section: Primary Open Angle Glaucomamentioning
confidence: 99%
“…1A). TM locates within iridocorneal angle and is the main pathway for drainage of aqueous humor [28]. In 1954, Barany found that perfusion of aqueous outflow system with testicular hyaluronidase (degrading enzyme for GAGs) could increase facility of outflow [29].…”
Section: Possible Pathogenesis Of Glaucoma In Mpssmentioning
confidence: 99%